Isolation and Characterization of Neural Stem Cells from the Rat Inferior Colliculus - Johannes Völker; Jonas Engert; Christine Völker; Linda Bieniussa; Philipp Schendzielorz; Rudolf Hagen; Kristen Rak (Hindawi Limited, 2019)
The inferior colliculus (IC) is a nucleus of the auditory pathway and its fourth relay station. It integrates afferent information from the superior olivary complex and the cochlear nucleus. To date, no causal therapeutic options are known for damaged neuronal structures in this area. Regenerative medicine offers a potential approach to causally treating hearing impairment. After neural stem cells had been identified in certain areas of the auditory pathway, the question arouses, whether the IC also has a neurogenic potential. Cells from the IC of postnatal day 6 rats were extracted and cultured as neurospheres. Cells in the neurospheres showed mitotic activity and positive stain of neural stem cell markers (Nestin, DCX, Atoh1, and Sox-2). In addition, single cells were differentiated into neuronal and glial cells shown by the markers β-III-tubulin, GFAP, and MBP. In summary, basic stem cell criteria could be detected and characterized in cells isolated from the IC of the rat. These findings will lead to a better understanding of the development of the auditory pathway and may also be relevant for identifying causal therapeutic approaches in the future.